The living clearly method : 5 principles for a fit body, healthy mind & joyful life - Baldwin, Hilaria (New York, New York : Rodale, 2016)
"Hilaria Baldwin knows what it means to be pulled in many directions-as a mother of three, businesswoman, yoga instructor, Instagram sensation, and wife of actor Alec Baldwin, she has to work hard to remain centered. Through her life experiences, struggles, and personal growth, Hilaria has developed a method for using movement and mindfulness to create an unbreakable mind-body connection, an illuminating method that shapes her life. The Living Clearly Method shows how to blend purposeful movement with conscious breath to move through our lives with grace, calm, and positivity. By using Hilaria's five simple principles-Perspective, Breathing, Grounding, Balance, and Letting Go-you can flow through any situation with the beautiful union of mind, body, and spirit that a yoga practice can create. But learning to honor the body and listen to the soul does not end when you get off the mat. Hilaria believes strongly in finding ways to integrate the five principles into your entire life, so for each step she also shares her own routines that keep her active all the time-from the little motions that engage her body during household chores and the foods that keep her well nourished to the philosophy that grounds her when she's being pulled in a million directions at once. This book is also packed with practical tools such as timesaving tips, delicious recipes inspired by clean and plant-based eating, mini-workouts that seamlessly integrate into your everyday life, breathing exercises, and customized yoga and meditation routines. The Living Clearly Method teaches you to listen to your body, tune in to your mind, and develop the consciousness to clear your head and find peace in your life. It is a beautiful, intuitive guide for living the healthiest life possible, both inside and out."--
Includes index.
Keywords: Meditation; Yoga; Stress management; Mind and body -- Meditations; HEALTH & FITNESS / Healthy Living; HEALTH & FITNESS / Yoga; BODY, MIND & SPIRIT / Meditation; COOKING / Health & Healing / General